6th IET International Conference on Power Electronics, Machines and Drives (PEMD 2012) 2012
DOI: 10.1049/cp.2012.0353
|View full text |Cite
|
Sign up to set email alerts
|

Reliability estimation of second life battery system power electronic topologies for grid frequency response applications

Abstract: This paper is part of a project which aims to research the opportunities for the re-use of batteries after their primary use in low and ultra low carbon vehicles on the electricity grid system. One potential revenue stream is to provide primary/secondary/high frequency response to National Grid through market mechanisms via DNO's or Energy service providers. Some commercial battery energy storage systems (BESS) already exist on the grid system, but these tend to use costly new or high performance batteries.Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Unfortunately, from a reliability perspective the greater the number of series connected cells, the lower the module reliability [5]. Therefore, low number of series connected cells within a module is a preferred approach.…”
Section: Index Terms-cascadedmentioning
confidence: 99%
“…Unfortunately, from a reliability perspective the greater the number of series connected cells, the lower the module reliability [5]. Therefore, low number of series connected cells within a module is a preferred approach.…”
Section: Index Terms-cascadedmentioning
confidence: 99%
“…Loss of Thevenin's equivalent resistance was taken into account in calculating efficiency of batteries; nevertheless, it did not address the impact of capacity inconsistency. Reference [17] calculated the reliability of different single phase battery-to-grid converter interfacing schemes. It found that second-life batteries were the least reliable part of the system.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research on the re-use of spent EV, PHEV batteries has focused on reliability estimation [1], optimal use strategy [2] and economic analysis [3,4]. Mukherjee et al [1] presented a reliability calculation method for a battery energy storage system, and designed a battery-to-grid converter topology for robust and reliable second-life batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Mukherjee et al [1] presented a reliability calculation method for a battery energy storage system, and designed a battery-to-grid converter topology for robust and reliable second-life batteries. Rule-based control is used to manage the charging and discharging of second-life batteries to extend their lifetime in [2], and realize commercial building peak load management and maximize cost savings.…”
Section: Introductionmentioning
confidence: 99%